Formulation and Evaluation of Vanishing Herbal Cream of Crude Drugs - Prajakta, Shinde; Shahu, Khule (Asian Journal of Pharmaceutical Research and Development, 2020)
The purpose of the present research work was to formulate and evaluate vanishing herbal cream. Herbal creams offer several advantages over other creams. The majority of existing creams which has prepared from drugs of synthetic origin and give extras fairness to face, but it has several side effects such as itching or several allergic reactions. Herbal creams do not have any of these side effects, without side effects it gives the fairness look to skin. Method carried out to prepare herbal cream was very simple. Firstly, oil phase was prepared, mixture of stearic acid (17%), potassium hydroxide (0.5%), sodium carbonate (0.5%) were melted at 700C. Secondly aqueous phase was prepared, mixture of alcoholic extract of crude drugs, including C. officinalis and A.indica, Turmeric, Nutmeg, Cinnamon, are commercially available as extracts and in different formulation to be used either for cosmetic purposes or for medical use. Glycerin (6%), perfume (0.5%), water (71%) heated at 70O c. Then aqueous phase was added into the oil phase at 70O c with continuous stirring. Now, once the transfer was completed it was allowed to come at room temperature all the while being stirred. Perfume was added at last just before the finished product was transferred to suitable container. The above prepared herbal cream was evaluated. The physical parameters such as pH, homogeneity by visual and by touch, appearance, wash ability, consistency, Patch test, irritancy test accelerated stability studies, type of smear were determined. Further studies are needed to investigate this formulation for its performance.